Weiqi Decoction Attenuated Chronic Atrophic Gastritis with Precancerous Lesion through Regulating Microcirculation Disturbance and HIF-1α Signaling Pathway. (20th June 2019) - Yin, Jing; Yi, Jinyu; Yang, Chun; Xu, Bo; Lin, Jiang; Hu, Hongyi; Wu, Xiaojun; Shi, Hailian; Fei, Xiaoyan
Abstract : Aim . Chronic atrophic gastritis (CAG), the precancerous lesions of gastric cancer, plays an important role in the stepwise process of gastric cancer. The ancient Chinese medicine believes in that Qi deficiency and blood stasis are involved in the pathogenesis of CAG. Weiqi decoction, a classical formula from Longhua Hospital, could supplement Qi and activate blood circulation of human beings and has been used for treating CAG in clinic over twenty years. The study aims to clarify the effect and underlying molecular mechanism of Weiqi decoction on CAG rats. Methods . Forty-eight male Wistar rats were divided randomly into six groups: control group, model group, folic acid group, and WQD-treated groups at doses of 4 g/kg, 2 g/kg, and 1 g/kg, with eight rats in each group. MNNG and saturated NaCl were used to induce CAG rat with precancerous lesion (intestinal metaplasia and dysplasia). After 40 weeks, gastric mucosal blood flow was measured using Laser Doppler Flowmetry. The pathological changes of the gastric mucosa were identified by H&E staining and AB-PAS staining. The protein expression of COX-2, HIF-1 α, VEGFR1, VEGFR2, Ki67, and cleaved caspase 3 in the gastric tissues was measured by western blotting approach. Gene expression of COX-2, HIF-1 α, VEGF, VEGFR1, VEGFR2, Ang-1, and Ang-2 was detected by using Quantitative PCR method. The PGE2 concentrations in serum were detected by ELISA method. The protein expression of Ki67 in gastric mucosa was also detected by immunohistochemistry. Results . Compared with control rats, atrophy and intestinal metaplasia as well as the microcirculation disturbance of gastric mucosa were induced in the stomach of CAG rats identified by the H&E and AB-PAS staining as well as microcirculation measurement, which could be significantly attenuated by WQD treatment. Moreover, compared with the control group, the protein and gene expression of COX-2, HIF-1 α, VEGFR1, and VEGFR2 in gastric tissues of pylorus was obviously increased and the serum PGE2 level was significantly deceased in CAG rats, which could be significantly counteracted by WQD administration. However, the gene expression of Ang-1 and Ang-2 was not significant difference between control rats and CAG rats, and WQD also had no significant effect on the gene expression of Ang-1 and Ang-2. Furthermore, the increased cell proliferation marked by upregulated protein expression of Ki67 and decreased cell apoptosis marked by downregulated protein expression of cleaved caspase 3 in stomach of pylorus in CAG rats were obviously reversed by WQD treatment. Conclusion . WQD attenuated CAG with precancerous lesion through regulating gastric mucosal blood flow disturbance and HIF-1 α signaling pathway.